Preliminary efficacy of a transdiagnostic parent-led internet-delivered intervention for children with anxiety and depressive symptoms: a pilot randomized controlled trial - Costina-Ruxandra Poetar; Anca Dobrean; Gerhard Andersson (BMC, 2024)
Abstract Background There is extensive research indicating that transdiagnostic interventions are effective for adults and children with anxiety and depressive disorders; however, limited research has been conducted on the efficacy of such programs targeting parents of children with anxiety and depressive symptoms delivered via the Internet. This study aims to investigate the preliminary efficacy of a transdiagnostic Internet-delivered intervention for Romanian parents of children with elevated anxiety and depressive symptoms. Methods We conducted a single-blinded pilot randomized controlled trial. Forty-two parents of children with anxiety and depressive symptoms (M age = 39.79, 78.6% women) from Romania were randomly assigned to one of the two groups, to ParentKIT, an Internet-delivered intervention based on Rational Emotive and Behavioral Therapy (n = 21), or to a delayed treatment condition (waitlist group) (n = 21). ParentKIT consisted of a brief transdiagnostic intervention delivered through nine modules with therapist guidance. Results A significant Group by Time effect was found for child emotional problems as reported by parents (Cohen's d = − 0.85) and for parental self-efficacy (Cohen's d = 0.71). Conclusion A transdiagnostic Internet-delivered intervention addressed to parents of children with elevated anxiety and depressive symptoms is a promising approach. Future research should include blind assessments as well as multiple outcome assessors and investigate the long-term efficacy of the intervention. Trial registration NCT05341297.